Optimal bank capitalization in crowded markets - Christoph Bertsch; Mike Mariathasan (Sveriges Riksbank, 2017)
We study banks' optimal equity buffer in general equilibrium and their response to under-capitalization. Making progress towards a "pecking order theory" for private recapitalizations, our benchmark model identifies equity issuance as individually and socially optimal, compared to deleveraging, as well as conditions that invert the individually optimal ranking. Imperfectly elastic supply of capital, incomplete insurance markets and costly bankruptcies give rise to inefficiently high leverage ex-ante, and to excessive capital shortfalls and insolvencies ex-post. Abstracting from moral hazard and informational asymmetries, we therefore provide a novel rationale for macroprudential capital regulation and new testable implications about banks' capital structure management.
Keywords: D5; D6; G21; G28; 330; Bank capital; recapitalization; macroprudential regulation; incomplete markets; financial market segmentation; constrained inefficiency